Environmentally-triggered contraction of the norovirus virion determines diarrheagenic potential - Helm, Emily W.; Peiper, Amy M.; Phillips, Matthew; Williams, Caroline G.; Sherman, Michael B.; Kelley, Theresa; Smith, Hong Q.; Jacobs, Sorin O.; Shah, Dhairya; Tatum, Sarah M.; Iyer, Neha; Grodzki, Marco; et al. (Frontiers in Immunology, 2022)
Noroviruses are the leading cause of severe childhood diarrhea and foodborne disease worldwide. While they are a major cause of disease in all age groups, infections in the very young can be quite severe with annual estimates of 50,000-200,000 fatalities in children under 5 years old. In spite of the remarkable disease burden associated with norovirus infections in people, very little is known about the pathogenic mechanisms underlying norovirus diarrhea, principally because of the lack of tractable small animal models. We recently demonstrated that wild-type neonatal mice are susceptible to murine norovirus (MNV)-induced acute self-resolving diarrhea in a time course mirroring human norovirus disease. Using this robust pathogenesis model system, we demonstrate that virulence is regulated by the responsiveness of the viral capsid to environmental cues that trigger contraction of the VP1 protruding (P) domain onto the particle shell, thus enhancing receptor binding and infectivity. The capacity of a given MNV strain to undergo this contraction positively correlates with infection of cells expressing low abundance of the virus receptor CD300lf, supporting a model whereby virion contraction triggers infection of CD300lflo cell types that are responsible for diarrhea induction. These findings directly link environmentally-influenced biophysical features with norovirus disease severity.